Pengaruh Evaluasi Kinerja, Tenure dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan - Suryani, Yunita Rahma Bintang; Swasti, Ika Korika (Journal of Business and Economics Research (JBE), 2025)
Human resource management (HRM) plays a crucial role in achieving the long-term goals of a company. PT Raya Bumi Nusantara Permai (RBNP) faces challenges in managing human resources, especially at Icon Mall Gresik. Although the mall has become the largest shopping center in Gresik, HR management faces issues such as subjective performance evaluations, differences in job satisfaction based on tenure, and fluctuations in employee motivation. Transparent performance evaluations, proper tenure management, and improved work motivation can address these issues, ultimately enhancing employee job satisfaction. This study aims to examine the effect of performance evaluations, tenure, and motivation on employee job satisfaction at Icon Mall Gresik. The research method used is explanatory research with a quantitative approach. Data were collected through a questionnaire distributed to 67 employees from four divisions. Data analysis was conducted using Partial Least Square (PLS) technique. The results show that performance evaluations, tenure, and work motivation contribute to employee job satisfaction. Performance evaluations have an impact through job mastery, where employees with adequate knowledge and skills feel more confident and productive, thus improving their job satisfaction. Tenure affects organizational commitment, where employees with longer tenure feel more appreciated and have better relationships with the company, positively impacting job satisfaction. Work motivation influences achievement, where employees who feel they have accomplished their work goals are more satisfied and motivated, which in turn increases their job satisfaction. Recommendations include that the company should improve performance evaluations, appreciate employee loyalty, and provide incentives to enhance motivation and job satisfaction.